Modelling in Medicine and Biology VI 2005
DOI: 10.2495/bio050131
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of embolic protection filters for carotid artery stenting

Abstract: Stroke is the third leading cause of death in the United States, accounting for 1.5 deaths reported per 1000 people. Carotid artery stenting (CAS) with cerebral protection is slowly becoming the gold standard for treatment of carotid artery occlusive disease in high risk patients. CAS is based on the selective cannulation of the common carotid artery by means of an introducer sheath or guiding catheter and the deployment of a wire mesh (stent) to treat the occluded artery segment. The goal for CAS is the preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Order and colleagues (12) found that the FilterWire EX missed the lowest percentage of small, medium, and large particles (5.81%, 2.99%, and 1.20%, respectively) in a severely tortuous idealized ICA in vitro. To our knowledge, the capture efficiency of the RX Accunet and Spider RX devices has been reported only by our laboratory (8,14–16). The present investigation correlates well with our previous in vitro work with vessels with constant cross-sections.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Order and colleagues (12) found that the FilterWire EX missed the lowest percentage of small, medium, and large particles (5.81%, 2.99%, and 1.20%, respectively) in a severely tortuous idealized ICA in vitro. To our knowledge, the capture efficiency of the RX Accunet and Spider RX devices has been reported only by our laboratory (8,14–16). The present investigation correlates well with our previous in vitro work with vessels with constant cross-sections.…”
Section: Discussionmentioning
confidence: 95%
“…The present investigation correlates well with our previous in vitro work with vessels with constant cross-sections. The RX Accunet had the smallest percentage of particles missed in vessels sized 5.0 mm, 5.5 mm, and 6.0 mm in diameter (0.42%, 0.16%, and 2.13%, respectively) (14,15). The FilterWire EZ also performed equally well for the 5.0-mm and 5.5-mm vessels (1.07% and 1.01%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Finol and colleagues tested, in vitro, the capture efficiency of Angioguard XP, FilterWire EZ and RX Accunet in straight silicone tubes of varying inner diameter (5.0, 5.5 and 6.0 mm) [16,17]. The bench-top flow system circulated distilled water at 180 ml/min at 80 mmHg.…”
Section: Results From Our Laboratory Performance Assessment: In Vitromentioning
confidence: 99%
“…We have previously conducted experimental and computational studies on DPDs used during CAS. Finol et al 8 investigated in vitro the performance of 3 DPDs (Angioguard XP, RX Accunet, and FilterWire EZ) in 3 vessel sizes (5.0-, 5.5-, 6.0-mm internal diameter). The devices performed best in the smallest tested vessel diameter.…”
Section: ¤ ¤mentioning
confidence: 99%